2022
DOI: 10.1177/13694332221132316
|View full text |Cite
|
Sign up to set email alerts
|

Stay cable vibration mitigation: A review

Abstract: Stay cables in cable-stayed bridges are subjected to various types of dynamic excitation mechanisms under environmental loads. The excited vibrations can have a large amplitude because of low vibration frequencies and small inherent damping of cables. As cables become longer (the longest cables are around 600 m in cable-stayed bridges with a main span of 1000 m), more modes are vulnerable to wind and rain-wind induced vibrations, posing challenges to vibration mitigation. This paper presents a comprehensive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 340 publications
(451 reference statements)
0
4
0
Order By: Relevance
“…According to equations (24a), (24b), and ( 19), the values of P 31 , P 32 , P 33 , and P 34 can directly determine the equivalent stifness and damping coefcients, thereby infuencing the active control force. In addition, equation (15) shows that P 31 , P 32 , P 33 , and P 34 can be determined from the ratio of β to α. Tus, the ratio of β to α plays an essential role in the active control force. Obtaining an appropriate value of β/α is critical for achieving the expected control performance.…”
Section: Lqr-based Design Approach Of the Active Control Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…According to equations (24a), (24b), and ( 19), the values of P 31 , P 32 , P 33 , and P 34 can directly determine the equivalent stifness and damping coefcients, thereby infuencing the active control force. In addition, equation (15) shows that P 31 , P 32 , P 33 , and P 34 can be determined from the ratio of β to α. Tus, the ratio of β to α plays an essential role in the active control force. Obtaining an appropriate value of β/α is critical for achieving the expected control performance.…”
Section: Lqr-based Design Approach Of the Active Control Systemmentioning
confidence: 99%
“…Te length and fexibility of stay cables increase continuously with the span of cable-stayed bridges, and with that comes the risk of large-amplitude parametric vibration [15]. It was found that if the inherent frequencies of the stay cable and bridge deck are close to a certain range, the largeamplitude parametric resonance of the cable would occur easily [16].…”
Section: Introductionmentioning
confidence: 99%
“…The length and flexibility of stay cables continuously increase with the span of cable-stayed bridges, which increases the risk of large amplitude parametric vibration [26]. If the inherent frequencies of the stay cable and bridge deck were close to a specific range, a large amplitude parametric resonance of the cable would easily occur [27].…”
Section: Introductionmentioning
confidence: 99%
“…The stay cables can accumulate energy and oscillate with substantial amplitudes. This oscillation rarely endangers the structural integrity of the works, but it is disturbing for users and can cause fatigue damage to the cable stays if it is not controlled [21].…”
Section: Introductionmentioning
confidence: 99%